Attainable sustainable : the lost art of self-reliant living - Bordessa, Kris (2020)
"Based on the blog of the same name, Attainable Sustainable shows readers how to live a simpler, more self-reliant life. It includes instructions not only for growing and cooking food but also for creating artisanal items for the home as well as navigating the great outdoors"--
Includes bibliographical references.
Keywords: Sustainability; Sustainable living; Self-reliant living